Improving the effect of non-uniform thermal distribution and electrical mismatch for PV Panel during partial shading condition - Abdul Hadi, Mohd Hanif; Mohd Shawal, Jadin; Norizam, Sulaiman; Airul Sharizli, Abdullah; Jun, Lee Woan (Springer Science and Business Media Deutschland GmbH, 2022)
Solar power is a sustainable energy source that generates electricity from the sun radiant. More than 114.9 GW of photovoltaic (PV) systems have been installed and commissioned in the world last year, which results in the new global total installed capacity at the end of 2019 reached at least 627 GW. However, the drawback of solar power is PV mismatch, generally due to partial shading condition (PSC). Hence, this research aims to analyse the effect of non-uniform thermal distribution and to improve the performance of the PV module under PSC. The experiment was held under different shading, and data were collected using MATLAB Simulink. The outcome reveals that with bypass diode improve the performance of the PV module under PSC. Moreover, mitigation from this drawback causes another problem, making maximum power point tracking (MPPT) hard to track global maximum power point (GMPP) because of multiple peaks to appear on the power versus voltage P–V graph.